The effects of exchange rate changes on palm oil export of Malaysia - Hassan, Mohd Khairul Hisyam; Yusoff, Mohammed; Zakaria, Intan Zanariah; Mohamad, Noorihsan (Universiti Putra Malaysia Press, 2008)
Malaysia now has become less dependent on the primary commodity exports to generate economic growth and employment. But the recent financial crisis had indicated that Malaysia should not underestimate the importance of its primary commodity sector. In particular, the palm oil export performed beyond expectations during the Asian financial crisis, which had to certain extent, cushioned the impact of financial crisis on the domestic economy.